Computerized Systems as a Driver of Employee Performance Improvement: Sistem Komputerisasi sebagai Pendorong Peningkatan Kinerja Karyawan - Rafiqa Magfirah Yusda; Said Zulkifli; Deandlles Christover; H.M.Z. Arifin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Computerized systems play a crucial role in enhancing work effectiveness and efficiency, particularly in government institutions, yet their implementation often faces technical obstacles that negatively impact employee performance. Specific Background: This study focuses on the Organizational Division of the Regional Secretariat of Paser Regency, where frequent system disruptions hinder the completion of administrative tasks. Knowledge Gap: Although many studies highlight the benefits of computerization, empirical research linking its influence to employee work effectiveness in local government settings remains limited. Aims: To analyze the effect of computerized systems on employee work effectiveness using measurable indicators. Results: A quantitative approach with the Spearman Rank Correlation technique on 18 respondents yielded an rs value of 0.529 > 0.472 (α = 0.05), indicating a significant positive relationship. Novelty: This study provides new empirical evidence on the contribution of computerized systems to improving work effectiveness in the regional public sector. Implications: The findings underscore the need to improve system quality and provide employee training to maximize technology utilization, thereby enhancing administrative performance and the quality of public services in Paser Regency Highlights: Significant positive correlation between computerization and work effectiveness. Highlights limited empirical studies in local government contexts. Emphasizes need for system improvement and employee training. Keywords: Computerized Systems, Work Effectiveness, Employee Performance, Public Administration, Local Government